The Everlasting Rose - Book 2 - Clayton, Dhonielle (Los Angeles, 2019)
Camille, Edel, and Remy, aided by The Iron Ladies and backed by alternative newspaper The Spiders Web, race to outwit Sophia, find Princess Charlotte, and return her to Orlǎns.
800
Accelerated Reader
Keywords: Beauty, Personal -- Fiction; Sisters -- Fiction; Dating (Social customs) -- Fiction; Counterculture -- Fiction; Newspapers -- Fiction; Beauty, Personal -- Fiction; Sisters -- Fiction; Dating (Social customs) -- Fiction; Counterculture -- Fiction; Newspapers -- Fiction